THEORIZING DIGITAL CULTURES - Bollmer, Grant; Ainsley, Michael (Los Angeles : SAGE, 2018)
Explaining how digital media affect identities, bodies, social relations, artistic practices and the environment, this book helps students understand the key theoretical approaches in the field.
Includes bibliographical references and index.
Keywords: Digital media -- Social aspects; Information society